Analisis variabel yang mempengaruhi sikap dalam membayar pajak bumi dan bangunan di kecamatan pasar kliwon Surakarta - Mawarni, Diyah; Saharsini, Astuning (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This reseacrh aims to determine the effect of taxpayer income, taxpayer awareness, quality of tax services and tax sanctions on compliance with paying land and building taxes in Pasar Kliwon District. The sampling technique in this study used purposive sampling for 100 land and building taxpayers with the criteria of owning or building a house or building locasted in Pasar Kliwon District. The data used are primary data obtained through a questionnaire. Data analysis in this study used multiple linear regression analysis with the help of SPSS version 19. The result of this study showed that taxpayer income, taxpayer awareness, and also the quality of tax services have a significant effect on tax compliance. On the other hand, tax sanctions have no significant effect on tax compliance. Synchronously, (simultaneously) taxpayer income, taxpayer awareness, quality of tax services, and tax sanctions affect tax compliance.